The Faculty of Medicine of the University of Maribor – the first ten years: Medicinska fakulteta Univerze v Mariboru – prvih deset let - Kranjc, Ivan (Acta Medico-Biotechnica, 2021)
The establishment of the Faculty of Medicine of the University of Maribor in the year 2003 and the beginning of a pedagogical process in the 2004/2005 academic year are those important points in the development of higher education system and growth of the local hospital which present an important achievement for the University of Maribor, health care, town and also the Republic of Slovenia. In the year when the Faculty of Medicine of the University of Maribor celebrates its tenth anniversary of operating, and in the year when the town Maribor records the 850th anniversary of its first written mention (1164, Castrum Marburch) the jubilee is getting a touch of a new milestone. In ten years the Faculty of Medicine has travelled its way to a contemporary, European comparable university study, faced Bologna reform and with relocation to the new construction in the direct vicinity of the fundamental educational base - today the University Medical Centre Maribor – ensured the foundation for further development, especially for expansion of the basic research activity.Telling is a piece of information that in our faculty more than 250 physicians have successfully completed their studies and who, in the period of extremly hard social and economic circumstances, with increasing frequency are looking for their opportunity for work and professional development abroad although they are very much needed at home, for one of the important reasons for the establishment of the second medical faculty in Slovenia was distinctly lack of physicians. The faculty has with the postgraduate study programme Biomedical technology offered also a contemporary doctoral study which to the ambitious, eager for new knowledge enables to realize numerous ideas, all with a purpose to facilitate as qualitative health care as can be. More than fourty Doctors of Science are already realizing their ideas, numerous among them have already been habilitated and are our esteemed professors who follow their predecessors.In front of our faculty there are numerous challenges - ten years is for such an institution a short period but a cross section of previous achievements which we, numerous authors, have gathered in this monography of which the outcome we expect on the celebration of the faculty, yet everything shows also new directions of development. Excellence on all levels is that which has to make us different, competitive to faculties with long tradition, we need to remain always a step ahead of others with the programme as much as with the pedagogical approaches and equipment. And importantly we need to open up into the world. Tasks for a new decade or perhaps more of them?